Synthesis, Characterization and Antioxidant Activity of 2-Aryl Benzimidazole Derivatives - Singh, Vineet Kumar; Parle, Amrita (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: To synthesize benzimidazole derivatives, characterize them by 1HNMR and ATIR techniques and evaluate their antioxidant activity. Methods: In the present study 19 benzimidazole derivatives were synthesized by reacting O-phenylenediamine as the primary reactant with different aromatic aldehydes and benzoic acids. Reactions were monitored using thin layer chromatography technique, and the newly synthesized derivatives were characterized by ATIR and 1HNMR techniques. The antioxidant assay was performed using ABTS [2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid)] method and DPPH [2,2-diphenyl-1-picrylhydrazyl] method. Results: Compounds BNZ-1, BNZ-2, BNZ-3, BNZ-9, and BNZ-10 showed comparable antioxidant activity to ascorbic acid at higher dose. Conclusion: The synthesized benzimidazole derivatives have significant radical scavenging potential.